Support for Digital VCR Functionality over Network for H.264/AVC - Pengpeng Ni; Isovic, D. (2008 IEEE International Conference on Communications, 2008)
In this paper, we propose a scalable video coding scheme for H.264/AVC video that fully utilizes the benefits of Switching frames (SP/SI) to facilitate user-friendly remote multimedia stream browsing and editing. A content aware rate-control algorithm is developed to adoptively determine the optimal encoding configuration for balancing the trade-off between video coding efficiency and temporal scalability. Our temporal scalable coding scheme is useful for implementing DVCR-like interactive functionality such as fast-forwarding and reversing in multimedia streaming applications such as Video-On-Demand, video broadcasting and remote video editing.